Efficient Selection Scheme for Incorporating Noncanonical Amino Acids Into Proteins in Saccharomyces cerevisiae - Tan, Linzhi; Zheng, Zhaohui; Xu, Yuanwei; Kong, Weikaixin; Dai, Zhen; Qin, Xuewen; Liu, Tao; Tang, Hongting (Frontiers in Bioengineering and Biotechnology, 2020)
With the advances in the field of expanded genetic code, the application of noncanonical amino acid (ncAA) is considered an effective strategy for protein engineering. However, cumbersome and complicated selection schemes limit the extensive application of this technology in Saccharomyces cerevisiae. To address this issue, a simplified selection scheme with confident results was developed and tested in this study. Based on a mutation library derived from Escherichia coli tyrosyl-tRNA synthetase (EcTyrRS), a logic gate in synthetic biology was used to optimize screening procedures. We found that an “and” gate was more suitable than an “or” gate for isolating aminoacyl-tRNA synthetase from S. cerevisiae. The successful incorporation of O-methyltyrosine (OMeY) proved the utility and efficiency of this new selection scheme. After a round of positive selection, several new OMeY-tRNA synthetase (OMeYRS) mutants were screened, and their incorporation efficiency was improved. Furthermore, we characterized the insertion of several tyrosine analogs into Herceptine Fab and discovered that OMeYRS and its mutants were polyspecific. One of these mutants showed an optimal performance to incorporate different ncAAs into recombinant proteins in S. cerevisiae; this mutant was cloned and transfected into mammalian cells, and the results proved its functionality in HEK293 cells. This study could expand the application of ncAA in S. cerevisiae to construct efficient yeast cell factories for producing natural and synthetic products.